Acute Achilles tendon rupture in badminton players - Fahlstrom, M.; Bjornstig, U.; Lorentzon, R. (The American Journal of Sports Medicine, 1998)
All patients with badminton-related acute Achilles tendon ruptures registered during 1990 to 1994 at the University Hospital of Umea were retrospectively followed up using a questionnaire. Thirty-one patients (mean age, 36.0 years), 27 men and 4 women, were included. Thirty patients (97%) described themselves as recreational players or beginners. The majority of the injuries (29 of 31, 94%) happened at the middle or end of the planned game. Previous local symptoms had been noticed by five patients (16%). Long-term results showed that patients treated with surgery had a significantly shorter sick leave absence than patients treated without surgery (50 versus 75 days). There was no obvious selection favoring any treatment modality. None of the surgically treated patients had reruptures, but two reruptures occurred in the nonsurgically treated group. There seemed to be fewer remaining symptoms and a higher sports activity level after the injury in the surgically treated group. Our results indicate that local muscle fatigue may interfere with strength and coordination. Preventive measures such as specific treatment of minor injuries and adequate training of strength, endurance, and coordination are important. Our findings also indicate that surgical treatment and careful postoperative rehabilitation is of great importance among badminton players of any age or sports level with Achilles tendon rupture.